Investigating the predictive effects of depression and self-esteem on suicide ideation among Malaysia east coast undergraduate students - Azlina Abu Bakar @ Mohd (Tanjung Malim, 2023)
Investigating the predictive effects of depression and self-esteem on suicide ideation among Malaysia east coast undergraduate students by Azlina Abu Bakar @ Mohd